A Ventosa como Tratamento para Dor e Disfunção Musculoesquelética: uma revisão sistemática - Ferreira, Laura Polli (2022)
The objective of this study was to evaluate the effects of cupping therapy on pain and function in musculoskeletal disorders, through a systematic review. A no-time limited search strategy was built with the following main terms cupping therapy , in the articles indexed in the Pubmed, Scopus and PEDro. To be included in the review, the studies had to be available as full text, be clinical trials focusing on treatment of injuries with dry cupping therapy. The others' types of cupping are excluded. Authors used PEDro scale to assess risk of bias in the included studies and presented the results by year of sample, groups, description of the cupping technique, evaluation outcome (p value). Results. 117 studies were identified, and 11 articles were enrolled in this review. Musculoskeletal conditions found were myofascial trigger-points, low back pain, neck pain, knee osteoarthritis, female chronic pelvic pain and carpal tunnel syndrome. Dry cupping showed effective in most articles (9/11); however, some articles do not have significant evidence of treatment compared to the control group (6/11). Conclusion. Dry cupping appears to be effective highlighting the treatment for pain and function. However, the authors observed no additional effects compared to another treatments or combined.